Impact of family care on sleep quality in perimenopausal women: mediating roles of anxiety and depression - Nana Liang; Jishun Ren; Juan Zhao; Xiaohui Liu; Haixia Zheng (BMC Women's Health)
Abstract Background This study aimed to investigate the relationship between family care, anxiety, depression, and sleep quality in perimenopausal women. Furthermore, it also aimed to examine the role of anxiety and depression in mediating family care and sleep quality. The study findings aim to provide theoretical support for alleviating anxiety and depression levels and improving sleep quality in perimenopausal women. Methods Perimenopausal women (n = 860) in Gansu Province were surveyed using the self-rating scale of sleep, self-rating anxiety scale, self-rating depression scale, and family adaptation partnership growth affection resolve. Results The sleep quality, anxiety, and depression scores of the perimenopausal women in Gansu Province were 25.33 ± 5.00, 40.74 ± 10.89, and 40.77 ± 10.03, respectively, and the family care score was 6.64 ± 2.36. Family care was negatively correlated with sleep quality, anxiety, and depression scores; anxiety was positively correlated with depression and sleep quality scores, and depression was positively correlated with sleep quality scores. Anxiety and depression in perimenopausal women partially mediated family care and sleep quality, with mediating effects accounting for 15.74% and 60.69% of the total effect, respectively. Conclusion Anxiety and depression are mediating variables between family care and sleep quality in perimenopausal women. It is recommended that hospital and community staff pay attention to the role of good family care in perimenopausal women, actively implement intervention strategies aimed at reducing anxiety and depression pathways, and improve their sleep quality.